2006
DOI: 10.1227/01.neu.0000245601.69451.27
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Encephalopathy in a National Football League Player

Abstract: Our first and second cases both had long careers without multiple recorded concussions. Both manifested Major Depressive Disorder after retirement. Amyloid plaques were present in the first case and completely absent in the second case. Both cases exhibited neurofibrillary tangles, neuropil threads, and coronary atherosclerotic disease. Apolipoprotein-E4 genotypes were different. Reasons for the contrasting features in these two cases are not clear. Further studies are needed to identify and define the neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
309
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(318 citation statements)
references
References 53 publications
5
309
0
4
Order By: Relevance
“…8,29 Studies showing the potential long-term effects of these injuries have put sports-related concussions under the national spotlight as a primary health concern. 16,35,36 Furthermore, there is concern that repetitive sub-concussive head impacts in sports may lead to neurocognitive deficits. 18,19,25 While limiting the number of head impacts in sports is an important component of reducing injury incidence, improving head protection is another essential element of injury mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…8,29 Studies showing the potential long-term effects of these injuries have put sports-related concussions under the national spotlight as a primary health concern. 16,35,36 Furthermore, there is concern that repetitive sub-concussive head impacts in sports may lead to neurocognitive deficits. 18,19,25 While limiting the number of head impacts in sports is an important component of reducing injury incidence, improving head protection is another essential element of injury mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed: (1) the formidable popularity of athletes continuing to play through possible mild to severe concussions, concealing any signs or symptoms from game personnel (there were unknown numeric concussion histories sustained by the retirees, but each assumed to have experienced at least 10, if not more); (2) the "warrior mentality" culture persists in all levels of hockey and sacrifices proper health and wellness care in order to be praised for playing through injuries; (3) the commonality of experiencing isolated feelings from sport and society when injured largely precipitated the first two findings; (4) long-term (specifically, 4 to 14 years) concussion symptoms emotionally and behaviorally resulted in anxiety and depressive effects, to include suicidal thoughts (cf., Omalu et al, 2006); and (5) retirees' post-hockey careers were restricted due to the lingering "daily reminders of their lost identities" (p. 176), which were provoked by ongoing headache and migraine symptoms.…”
Section: Consequences Of Concussion Severitymentioning
confidence: 99%
“…This appears to occur largely alongside the difficultly in assessment, diagnosis, and management of sports-related concussion (e.g., Carroll, 2012;McCrory et al, 2013). Corresponding with the prevalence of recurrent concussion, though, researchers have found that athletes' concussion histories are associated with cognitive impairment (Bleiberg et al, 2004;Cancelliere et al, 2014;Thornton, Cox, Whitfield, & Fouladi, 2008), depression, anxiety, and suicidal thoughts (Caron et al, 2013;Omalu et al, 2006), and signs of lower mental health scores later in life (Guskiewicz et al, 2005).…”
mentioning
confidence: 99%
“…In the article, Omalu et al contended that Webster's brain showed features consistent with chronic traumatic encephalopathy (CTE), a neurodegenerative condition most commonly observed in boxers (Omalu et al, 2005). The May 2006 issue of Neurosurgery featured a scathing critique of Omalu et al's article, arguing that it perpetrated a "serious misconception", and denying the finding of CTE.…”
Section: Clinical Uncertaintymentioning
confidence: 99%